Pengaruh Metode Index Card Match dalam Pelajaran Al-Qur’an Hadist terhadap Hasil Belajar Siswa Kelas X Madrasah Aliyah - Maulidina Rahmawati; Sulaiman Sulaiman (AS-SABIQUN, 2022)
The lack of variety in the learning strategies used and the poor performance of MAS Asy Syarif Koto Laweh class X students in Al-Qur'an Hadith subjects were the driving forces behind this study. 1) To understand the learning process utilizing the tag matching method is the goal of this study. 2) Using the tag matching method, determine the learning results. 3) to assess the impact of the card matching technique. A Hadith lecture on student learning outcomes uses card comparison to "match votes in Al-Qur." Asy Syarif Koto Laweh Tilatang Kamang for XMAS. Experimental quantitative research is used in this work. Students in class X made up the population of this study. Three students were created by combining IPA and X IPS MAS Asy Syarif Koto Laweh. The method of sampling used in this investigation was to sample 34 pupils from MAS Asy Syarif Koto Laweh's class X in total. Documents, tests, and questionnaires were used to gather data. With the use of the card matching method as the independent variable and student learning outcomes as the dependent variable, data analysis was conducted using simple linear regression analysis using SPSS version 26. Considering the findings of the research and the results of the survey 1) Up to 12% of students are qualified when the index card matching method is used at an average (average) level of 109.65. 2) The average score of 90.15 to 29% of the students in the top category speaks to the academic performance. 3) There is a connection between the card-matching technique and students' in-class learning outcomes. The R-squared test result of 0.624 (62.4%) reveals that there is a relationship between the independent variable arrangement and the dependent variable for X MAS Asy Syarif Koto Laweh.